2005
DOI: 10.1128/aem.71.6.3342-3347.2005
|View full text |Cite
|
Sign up to set email alerts
|

Genomic DNA Amplification from a Single Bacterium

Abstract: Genomic DNA was amplified about 5 billion-fold from single, flow-sorted bacterial cells by the multiple displacement amplification (MDA) reaction, using 29 DNA polymerase. A 662-bp segment of the 16S rRNA gene could be accurately sequenced from the amplified DNA. MDA methods enable new strategies for studying nonculturable microorganisms.The multiple displacement amplification (MDA) reaction uses the 29 DNA polymerase and random primers to amplify DNA templates (1-3, 5-6). Amplification from small specimens ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
268
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(273 citation statements)
references
References 7 publications
4
268
0
1
Order By: Relevance
“…The purpose of the lysis step is to degrade the microbial cell envelope without damaging the chromosomal DNA, introducing contamination or inhibiting subsequent amplification reactions. The majority of single-cell studies rely on an alkaline lysis procedure first described by Raghunathan et al 21 , although alternative or supplementary treatments such as heat, freeze-thaw, detergents and treatment with hydrolytic enzymes have been used 6 . However, these lysis techniques are not universally effective on all microbes, and thus a substantial fraction of genomes may not be recovered from some environmental samples.…”
Section: Experimental Designmentioning
confidence: 99%
“…The purpose of the lysis step is to degrade the microbial cell envelope without damaging the chromosomal DNA, introducing contamination or inhibiting subsequent amplification reactions. The majority of single-cell studies rely on an alkaline lysis procedure first described by Raghunathan et al 21 , although alternative or supplementary treatments such as heat, freeze-thaw, detergents and treatment with hydrolytic enzymes have been used 6 . However, these lysis techniques are not universally effective on all microbes, and thus a substantial fraction of genomes may not be recovered from some environmental samples.…”
Section: Experimental Designmentioning
confidence: 99%
“…Hutchison et al (2005) discovered that a smaller MDA reaction volume (3 ml) greatly reduced the amount of nonspecific DNA generated with 50 molecules of singlestranded circular M13 template compared to higher reaction volumes (15 or 30 ml). Others have shown that the total number of DNA templates affects representational bias (Lasken et al, 2005), with a single copy of template giving the highest bias (Raghunathan et al, 2004). Reducing bacterial DNA template from 10 ng (410 6 genome copies) by 10-and 100-1000-fold reduced representational bias 3-and 6-fold, respectively (Wu et al, 2006).…”
Section: A Brief History Of Mdamentioning
confidence: 99%
“…Progress has been made in the ability to analyze genomes, without the prerequisite of cultivation, by using MDA from individual cells. The first demonstration of genomic sequencing from single cells used E. coli isolated by fluorescence-activated cell sorting, followed by MDA (Raghunathan et al, 2004). Amplification of B5 fg of template generated B24 mg of product, more than a billion-fold amplification.…”
Section: Use Of Mda In Microbial Ecologymentioning
confidence: 99%
“…However, MDA from a single cell suffers from amplification bias. The single chromosome copy is broken into DNA fragments, further adding to amplification bias, and any contaminating DNA can also contribute to the sequences obtained (Raghunathan et al 2005;Woyke et al 2011). It is therefore generally not possible to finish a microbial genome starting from a single cell (Rodrigue et al 2009).…”
mentioning
confidence: 99%